1992
DOI: 10.1080/0266736920080305
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Supervision for Newly Qualified Educational Psychologists

Abstract: It is increasingly recognised that professional development is a long-term if not a life-time activity and does not end with initial 'qualification'. Most professions now acknowledge the need (requirement or even entitlement) for continuing professional development (CPD) following initial qualification; some professions are even able to require newly qualified entrants to accumulate a specified number of CPD 'units'over their first few years, other professions require a 'probationary year', and other professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…The explicit lack of a discussion of the authors' epistemological and theoretical stance, which informed their choice of methodology, which in turn did not allow for an adequate lack of exploration of some potentially important findings, were a serious limitation of these three articles. Lunt and Sayeed (1995) followed up a previous piece of research Sayeed and Lunt (1992) which used postal questionnaires and a series of structured interviews with newly qualified EPs and Principal Eductional Psychologists to investigate the experience of induction. The authors justified the selection of newly qualified EPs by proposing that the first year of practice as a newly qualified EP was a year where practitioners were still learning the practicalities of the job and trying to assimilate the theoretical elements into everyday practice.…”
Section: Discussion and Critical Review Of Studiesmentioning
confidence: 99%
“…The explicit lack of a discussion of the authors' epistemological and theoretical stance, which informed their choice of methodology, which in turn did not allow for an adequate lack of exploration of some potentially important findings, were a serious limitation of these three articles. Lunt and Sayeed (1995) followed up a previous piece of research Sayeed and Lunt (1992) which used postal questionnaires and a series of structured interviews with newly qualified EPs and Principal Eductional Psychologists to investigate the experience of induction. The authors justified the selection of newly qualified EPs by proposing that the first year of practice as a newly qualified EP was a year where practitioners were still learning the practicalities of the job and trying to assimilate the theoretical elements into everyday practice.…”
Section: Discussion and Critical Review Of Studiesmentioning
confidence: 99%
“…Annan and Ryba (2013) advocated the fundamental importance of supervision to sound professional practice in school psychology, while Smith Harvey and Pearrow (2010) suggested that it is imperative for professional growth and skill development. Sayeed and Lunt (1992) and Smith Harvey and Stuzziero (2008) suggested that for school psychologists, supervision should be a long term, if not life-long activity. Despite this, internationally there have been consistent reports of school psychologists receiving insufficient or inadequate supervision (Chafouleas, Clonan, & Vanauken, 2002;Crespi & Dube, 2006;Lam & Yuen, 2004;Thielking, Moore, & Jimerson, 2006).…”
Section: Supervision Of School Psychologistsmentioning
confidence: 99%
“…Within the literature, the supervision of school psychologists falls into three main areas (Dunsmuir & Leadbetter, 2010): The supervision of practising school psychologists (e.g. Annan & Ryba, 2013; Chafouleas et al., 2002; Lam & Yuen, 2004; Smith Harvey & Pearrow, 2010; Thielking et al., 2006); the supervision of school psychologists in training (Atkinson & Woods, 2007; Carrington, 2004; Haboush, 2003; Hill et al., 2015; Sayeed & Lunt, 1992; Woods et al., 2015); and the supervision of professionals from other disciplines by school psychologists (Callicott & Leadbetter, 2013; Maxwell, 2013; Osborne & Burton, 2014). The empirical element of this article focuses on the second of these, given that the need for supervision is considered to be particularly important during professional training and critical to ensuring both the effectiveness of practice placements and the experience of the trainee (Woods et al., 2015).…”
Section: Supervision Of School Psychologistsmentioning
confidence: 99%